Two New Alkaloids from the Marine‐Derived Fungus Penicillium sp. LSH‐3‐1. Issue 6 (1st June 2022) - Li, Sihui; Ma, Yihan; Wang, Lixia; Lan, Donghe; Fu, Leilei; Wu, Bin
Abstract: Two new alkaloids, peniokaramine (1 ) and penipyranopyridine (6 ), along with seven known compounds, were isolated from the marine‐derived fungus Penicillium sp. LSH‐3‐1. Their structures were elucidated from UV, IR, MS, 1D and 2D NMR spectroscopic data. The anti‐inflammatory potential of compounds 1 –8 in LPS‐induced RAW264.7 cells was detected, revealing that compounds 3 and 5 significantly decreased LPS‐induced production of pro‐inflammatory mediators, including NO, IL‐6 and TNF‐α. Compounds 1 –8 were also screened for their cytotoxic activity against A549 cells and compound 1 showed moderate activity. Abstract :